PENGARUH KINERJA OPERASIONAL TERHADAP KEPUASAN KONSUMEN - Muhammad Natsir (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to determine the influence of variables there any operational performance of the RPA customer satisfaction PT. Ciomas both simultaneously and partially, and to know which is more influential among variables operational performance of consumer satisfaction RPA PT. Ciomas. This study was carried out to customers RPA PT Ciomas which has transact more than one year. This study is a qualitative research method and an explanatory research design (explanatory research). Total sample of 37 customers RPA PT. Ciomas. Data were analyzed using univariate and bivariate analysis. The results showed there was a significant relationship between the variables operational performance to customer satisfaction (p <0.01), with the flexibility variables (X1) which affect very effective in improving the level of customer satisfaction.